AKTUALISASI NILAI PANCASILA DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA - I Wayan Tagel Eddy (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2018)
The dynamics in actualizing the value of Pancasila into the life within the society, nationship and citizenship is a necessity, so that Pancasila remains a relevant paradigm in providing guidance for policy making and problem solving in the life of nationship as well as citizenship. Hence, the loyalty of the citizens to Pancasila remains in the high level. On the other hand, apathy and resistance to Pancasila can be minimized. The substance of the dynamics in the actualization of Pancasila values in the life of praxis is always the change and renewal in transforming the value of Pancasila into the norms and practices of life by maintaining consistency, relevance, and contextualization. While continuous change and renewal occurs when there is internal dynamics (self-renewal) and the absorption of foreign values that are relevant for the development and instilment of ideology Pancasila. The outcomes of all efforts to change and renewal in actualizing the value of the Pancasila is the tolerance of acceptability and credibility of Pancasila by the citizens of Indonesia.